2021
DOI: 10.1002/pi.6314
|View full text |Cite
|
Sign up to set email alerts
|

Mono‐filler and bi‐filler composites based on thermoplastic polyurethane, carbon fibers and carbon nanotubes with improved physicomechanical and engineering properties

Abstract: Two types of carbon-based fillers, i.e. multi-walled carbon nanotubes and carbon fibers, were incorporated into thermoplastic polyurethane (TPU) through melt mixing to prepare mono-filler and bi-filler composites. It was evaluated as to how much the properties of bi-filler composites were different from those of their mono-filler counterparts. Attenuated total reflectance Fourier transform infrared (ATR-FTIR) and time sweep rheological measurements were employed to study the microphase separation of TPU. The q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
37
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 42 publications
0
37
0
Order By: Relevance
“…In this section, the impacts of various parameters on the CNT network percentage after the percolation threshold (f) is met are explained. Figure 3 displays the variation of "f" at different "Lc" values based on Equation (17). A low "Lc" caused a high "f", but "f" reduced considerably at a high "Lc".…”
Section: Percentage Of Networked Cntsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this section, the impacts of various parameters on the CNT network percentage after the percolation threshold (f) is met are explained. Figure 3 displays the variation of "f" at different "Lc" values based on Equation (17). A low "Lc" caused a high "f", but "f" reduced considerably at a high "Lc".…”
Section: Percentage Of Networked Cntsmentioning
confidence: 99%
“…Carbon nanotubes (CNTs) endow significant conductivity and high mechanical properties to composites, especially polymer CNT nanocomposites (PCNT) [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 ]. A CNT aspect ratio in a range of 500–1000 creates a conductive network at extremely low concentrations of CNTs [ 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…There are numerous reports about the physico-mechanical properties of single-walled (SWCNTs) and multi-walled carbon nanotubes (MWCNTs) filled polymer systems. [6][7][8][9][10][11][12][13][14][15][16][17][18][19] Razavi-Nouri [6,7] studied the effect of SWCNTs on dynamic mechanical properties and non-isothermal crystallization kinetics of polypropylene (PP). It was found that the maximum storage modulus (G') was obtained for the material containing 1 wt% SWCNTs.…”
Section: Introductionmentioning
confidence: 99%
“…Rostami et al have worked on the systems based on a thermoplastic polyurethane (TPU) reinforced with MWCNTs, [ 15 ] hybrid of functionalized graphene nanoplatelets (fGnPs) and functionalized MWCNTs (fMWCNTs), [ 16 ] and also mono‐filler and hybrid of carbon fibers (CFs) and MWCNTs. [ 17 ] They reported that the extent of phase separation of TPU soft and hard segments increased with the increase in MWCNTs concentration. [ 15 ] It was found that the nanocomposites containing both of fGnPs and fMWCNTs had a positive deviation from the law of mixtures in their mechanical, thermal and electrical properties.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation